An increased incidence of SGA persists in areas of multiple deprivation despite a decade of increased social intervention: insights from the Leeds Cohort Study 2000–2008. (16th November 2010) - Khadim, B; Greenwood, D; Thomas, M; Tebbutt, E; Talbot, H; Simpson, N
Abstract : Introduction: Deprivation is a known risk factor for low birthweight and adverse neonatal outcome. The authors set out to characterise the impact of social intervention strategies within the most deprived areas in Leeds. IMD fifth RR for SGA (95th CI) First (least deprived) 1 Second 1.2 (1.1 to 1.3) Third 1.6 (1.4 to 1.8) fourth 1.9 (1.7 to 2.1) Fifth (most deprived) 2.0 (1.9 to 2.2 Methods: Maternal and neonatal data were gathered from the maternity system for the years 2000–2008. Information collected included birthweight, gestational age (GA) at delivery and maternal postcode. Small-for-gestational age (SGA) was indicated for babies falling below the 10th centile of birthweight for their GA. Indices of Multiple Deprivation (IMD) were assigned using the 2004 classification, and the 152 medium sized output areas divided into five equal groups to represent the spectrum of deprivation within Leeds. 32 of the 44 SureStart centres within Leeds were located within the most deprived fifth. Poisson regression was used to model rates of SGA by year, together with IMD category. Results: 65 535 deliveries were recorded over the study period. 8.3% of births were SGA, ranging from 5.4% in the least deprived fifth, up to 11.0% in the most deprived fifth. There was a stepwise increase in the incidence of SGA with increasing deprivation: The gap between most and least deprived groups narrowed marginally between 2000 and 2008, but this was not statistically significant (p=0.2). Conclusion: These data suggest that further community strategies are likely to be required in order to reduce the incidence of SGA in deprived areas.